Analysis and Visualization Data of Covid-19 Based on Scopus - Tupan, Tupan; Rosiyan, Nur Rizzal (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2021)
This study analyzes the amount of documentation about COVID-19 by year, publication source, institution, country, type of document, and funding agency and maps it based on keywords. The research data was obtained through the Scopus database with the keywords novel corona virus or corona virus 2019 or covid 2019 and covid 19, which were further explored. For mapping, the Covid 19 data, the VOSviewer software was used. The findings show that there are 723 covid 19 documents, 569 of which can be accessed openly and 154 can be accessed by subscription. Most of the COVID-19 data published in the Journal of The American College of Radiology with the subject categories discussed were radiology, nuclear medicine, and imaging. Huazhong University of Science and Technology is the most productive institution in producing covid 19 data. China is the country that produces the most covid data. The most type of Covid 19 data documents are articles with the most medicine subject category. Most of the funding sponsors were awarded by the National Science Foundation of China. The visualization of the covid 19 data was mapped into 5 clusters with the most groups from each cluster being cluster 1 being severe acute respiratory syndrome coronavirus, cluster 2 coronavirus disease 2019, cluster 3 fever (fever), cluster 4 epidemiology, cluster 5 disease severity.